Integrated Employee Database System for South Sumatra’s Tourism and Culture Department - Marlindawati, .; Misinem, .; Indah, Apriliani (INTI International University, 2024)
The management of employee data in many governmental organizations remains entrenched in outdated, manual processes that are inefficient and prone to errors. This issue was notably present at the South Sumatra Province Culture and Tourism Office, where the existing method of using Microsoft Excel and Word for handling employee records was becoming increasingly untenable. The manual system not only required excessive administrative effort but also exposed the organization to significant risks of data loss and errors, which are detrimental to effective human resource management. To address these challenges, a web-based information system was developed using the PHP programming language. This system was designed to automate and streamline the entire process of managing employee data, from entry to retrieval and reporting. The system includes several key components: a secure login page, a profile page for quick access to important data, dedicated pages for managing specific types of information such as employee details and position data, and a comprehensive reporting page for generating actionable insights from the data collected. The results of implementing this new system were transformative. It significantly reduced the time and effort required to manage employee data, improved the accuracy of the data stored, and enhanced the security measures protecting sensitive information. The system's user-friendly interface and robust functionality were well-received by the staff, facilitating smooth adoption and integration into daily operations. The new web-based information system has successfully modernized the administrative functions of the South Sumatra Province Culture and Tourism Office. It has established a more reliable, efficient, and secure framework for managing employee data, setting a strong example for similar advancements in other governmental departments. Future recommendations include ongoing updates to the system and continuous training for users to ensure it continues to meet the evolving needs of the organization